ETYMOLOGICAL ANALYSIS OF SOME DRESS NAMES IN UZBEK AND ENGLISH LANGUAGES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the etymological origins of selected dress names in the Uzbek and English languages. Clothing terminology represents a historically layered lexical field formed under the influence of cultural contact, trade relations, social development, and technological progress. The study aims to identify the sources of origin of dress names, trace their historical development, and reveal the cultural factors reflected in their etymology. The research employs etymological, comparative, and semantic analysis methods. The findings show that Uzbek dress names are largely influenced by Turkic, Persian, and Arabic sources, whereas English dress terminology reflects Germanic roots alongside strong borrowings from French, Latin, and other European languages. The study highlights the role of etymology in understanding cultural identity and historical interaction.